Synthesis, characterization and antiproliferative activity of seco analogues of brassinosteroids - Kvasnica, Miroslav; Buchtova, Katerina; Budesinsky, Milos; Beres, Tibor; Rarova, Lucie; Strnad, Miroslav (Steroids, 2019)
Synthesis and structure-activity relationship analysis of a two groups of 2,3-seco analogues of brassinosteroids (BRs) were performed to examine their antiproliferative activities. Two steroid skeletons were chosen for the preparation of seco analogues - cholestane and stigmastane. The synthetic strategy consists of multistep reactions and detailed analysis of compounds prepared. We have discovered unpublished behaviour of 2,3-seco-2,3-dihydroxy-6-ketones leading to formation of intramolecular ketal with two new steroidal rings. Their reaction intermediates were also characterized in some cases. All compounds prepared were fully characterized with NMR and MS techniques. Most of compounds were tested for in vitro cytotoxicity on three cancer cell lines (CEM, MCF7, and HeLa) and normal human fibroblasts (BJ). It was discovered that some seco analogues caused apoptosis in cancer cells. The most promising seco derivative 28 proved to have high therapeutic index.
Keywords: HeLa Cells; proliferace buněk; apoptóza; techniky syntetické chemie; Apoptosis; screeningové testy protinádorových léčiv; Brassinosteroids; MFC-7 buňky; Structure-Activity Relationship; lidé; HeLa buňky; Antineoplastic Agents; MCF-7 Cells; protinádorové látky; Chemistry Techniques, Synthetic; Cyclization; Seco analogues; Cell Proliferation; vztahy mezi strukturou a aktivitou; Drug Screening Assays, Antitumor; Skeletal modification; Cytotoxicity; brassinosteroidy; Humans